A framework for targeting and scaling-out interventions in agricultural systems - Herrero, Mario; Notenbaert, An Maria Omer; Thornton, Philip K.; Pfeifer, Catherine; Silvestri, Silvia; Omolo, Abisalom; Quirós, Carlos F. (2014)
There are real needs and opportunities for well-targeted research and development to improve the livelihoods of farmers while at the same time addressing natural resource constraints. The suitability and adoption of interventions depends on a variety of bio-physical and socio- economic factors. While their impacts -when adopted and out-scaled- are likely to be highly heterogeneous, not only spatially and temporally but also in terms of the stakeholders affected. In this document we provide generic guidelines for evaluating and prioritising potential interventions through an iterative process of mapping out recommendation domains and estimating impacts. As such, we hope to contribute to the inclusion of such important considerations when agricultural innovations are targeted and scaled out.